8. OCCUPATIONAL BURNOUT AMONG MEDICAL STAFF AT THE DEPARTMENT OF SURGERY - ANESTHESIA AND RESUSCITATION, HUNG VUONG HOSPITAL IN 2023 (Vietnam Journal of Community Medicine, 2024)
Objective: This study was carried out to describe the current situation of occupational burnout among medical staff at the Department of Surgery-Anesthesiology and Resuscitation (SAR), Hung Vuong Hospital in 2023.Methods: This was a cross-sectional design study. The sample size for quantitative research is all 155 medical staffs currently working at the Department of SAR. Data were collected using Maslach’s scale (MBI-HSS 22 questions).Results: The overall rate of medical staff with signs of occupational burnout was 62.5% (high level was 33.5%, average level was 29.0%); Occupational burnout was most common in the aspect of emotional exhaustion (62.6%), personal achievement (56.1%), and lastly, depersonalization (41.3%). The rate of high levels of burnout was more common in men, work experience 6 times/month, working time >48 hours/week and overtime (p
Keywords: Occupational burnout, medical staff, surgery - anesthesia and resuscitation.